Análise das variáveis temporais de jogo nas classes do tênis de mesa paralímpico: um estudo exploratório - Almeida, Raphael Moreira de [UNIFESP] (2020)
The analysis of the temporal game structure applied to table tennis allows the identification of variables such as the rally duration - DR, rest time - RT, number of shots per rally - NS, effort and rest ratio - E:R, rate of shots per rally - RS and total match duration – TMD. Studies with able-bodied table tennis found DR of approximately 3.5 seconds, RT between 8 to 20 seconds and E:R from 0.12 to 0.50. Para table tennis has eleven classes, which integrates different types and levels of physical and intellectual disabilities and understanding the characteristics of each class would be useful for the ideal and specific training prescription and to support the classification. The aim of this study was to identify the temporal game structure in the eleven classes of para table tennis and to compare the classes within their groups (wheelchair, standing and intellectual disability) and genders. For this, 147 matchs from 21 classes (11 male and 10 female) played in the 2018 Singles World Championship were analyzed. The variables analyzed were: DR, RT, NS, E:R, RS and TMD. The results showed DR between 3 and 4.5 seconds, RT between 9 and 15 seconds, NS between 3 and 6, E:R between 0.20 and 0.40, RS between 0.96 and 1.26strokes/s and TMD between 18 and 35 minutes, most of them similar to those found in able-bodied table tennis. Among the most relevant differences found in the comparisons between classes and genders are the highest values of DR and NS for men in relation to women in all classes of wheelchair group, as well as the lowest values of the same variables in classes with more severe physical limitations (Class 1 and 2) of the wheelchair group in relation to the others. Men's Class 3 and 4 had DR greater than all other classes in both groups and greater than table tennis. Standing Classes 6, 8 and 11 had the highest values of DR and NS among the standing group (both genders), as well as Class 7 had the lowest values of the same variables in both, which indicates that the characteristics of the class for both genders are similar. The RS of the highest classes (3, 4 and 5) of wheelchair group were higher than the classes of standing, intellectual disability and able-bodied table tennis and indicate a different pattern in the game of these classes (higher frequency of strikes per second.). The RT fluctuated from 9 to 15 seconds and may have interference from ball catchers. The results in our study can serve as initial references for training programs specific to para table tennis, which respect the characteristics of the game regarding physical limitations, type of disability, class characteristics and sex. In addition, they can serve as a reference for a more efficient classification system, which takes into account the temporal game structure of the classes.